Antiobesity effect of brewer's yeast biomass in animal model. (April 2019) - Chang, Chih-Ling; Kao, Tsai-Hua
Graphical abstract: Highlights: Four prenylflavonoids and six hop bitter acids were found in brewer's yeast biomass. Content of hop bitter acids was higher than that of prenylflavonoids in BYB. Both BYB ethanol extract and BYB supernatant showed anti-obesity effect. BYB ethanol extract showed more anti-obesity effect than BYB supernatant. Abstract: Brewer's yeast biomass (BYB) is a byproduct of the beer-brewing process. This study explored the inhibition effect of BYB on obesity using an animal model. The prenylflavonoid and hop bitter acid contents of BYB were also evaluated to identify possible active substances. BYB ethanol extract contained four prenylflavonoids and six hop bitter acids. The content of hop bitter acids was higher than that of prenylflavonoids. Feeding Sprague–Dawley rats with 50 or 250 mg/kg BW doses of BYB ethanol extract and 250 mg/kg BW of BYB supernatant was found to significantly reduce tissue fat weight, serum triglyceride and hepatic triglyceride, serum insulin and HOMA-IR, as well as to increase liver antioxidant activity. Moreover, BYB ethanol extract could inhibit increased weight, feed efficiency, heparin-releasable lipoprotein lipase enzyme activity, and thiobarbituric acid reactive substance in liver. In particular, low doses of BYB ethanol extract could enhance lipolysis.